Gendered Violence at International Festivals: An Interdisciplinary Perspective - Platt, Louise; Finkel, Rebecca (Routledge, 2020)
Gendered Violence at International Festivals is a groundbreaking collection that focusses on this highly important social issue for the first time. Including a diverse range of interdisciplinary studies on the issue, the book contests the widely held notion that festivals are temporal spaces free from structural sexism, inequalities or gender power dynamics. Rather, they are spaces where these concerns are enhanced and enacted more freely and where the experiential environment is used as an excuse or as an opportunity to victim blame and shame. In this emerging and under-researched area, the chapters not only present original work in terms of topics but also in theoretical and methodological approaches. All of the chapters are cross- or interdisciplinary, drawing on gender, sexualities, cultural and ethnicity studies. Studies from a range of highly regarded academics based around the world examine the subject by looking at examples from a wide range of destinations, including Spain, Argentina, Nigeria, Zimbabwe, Australia, Canada and the UK. This significant book progresses understanding and debates about gendered festival experiences and emphasises the symbolic and physical violence often associated with them. This will be of great interest to, undergraduate and postgraduate students and academics in the field of Events Studies. It will also be of use to practitioners or non-profit workers in the festival industries, including festival management organisations and planning committees.
Google-Books-ID: Q6bYDwAAQBAJ
Keywords: Business & Economics / Industries / Hospitality; Travel & Tourism